Innovation Hub How-To: Lessons From Silicon Valley - Berger, Andreas; Brem, Alexander (Global Business and Organizational Excellence, 2016)
Firms around the world are eager to replicate the successes of enterprises that have established innovation labs in California's Silicon Valley. An analysis of four leading US companies that have set up idea incubators in the Valley—Xerox, Apple, Google, and Cisco—point to eight factors for success in establishing an innovative environment: carefully considering the decision to set up such a center, hiring the right people, designing a framework for effective output, creating a buffer from bureaucratic distractions, securing a leader to champion the effort, focusing on business outcomes, fostering disruptive over incremental innovation, and being patient. Regardless of where an innovation hub is established, the key to success lies in hiring creative, intrinsically motivated staff and then giving them the freedom to do what they do bes